Perancangan Dashboard Monitoring Pasien Pada Fasilitas Kesehatan XYZ - Faithtria, Monica Glory; Trisnawarman, Dedi (STMIK Banjarbaru, 2024)
Health is the most important thing in social life, in the era of globalisation the improvement of services at health facilities is required to have high value. In the face of competition in the current era of globalisation, health facilities require quality improvement to change Business Intelligence. This research aims to design a visit monitoring dashboard at XYZ health facilities. The software engineering method used is the prototyping method. In this method, Key Performance Indicator (KPI) identification is added to determine the appearance of the dashboard visualisation. In the results of the design, the dashboard visualisation designed using the Microsoft Power BI tool, will display graphic diagrams that show data, as well as in the form of numbers in the form of KPIs. Tests that have been carried out will provide improved services.Keywords: Business Intelligence; Dashboard; Prototyping; Key Performance IndicatorÂ AbstrakKesehatan merupakan hal terpenting dalam kehidupan bermasyarakat, pada era globalisasi peningkatan pelayanan pada fasiilitas kesehatan dituntut memiliki nilai yang tinggi. Dalam menghadapai persaingan pada era globalisasi pada saat ini, fasilitas kesehatan memerlukan peningkatan kualitas berubah Business Intelligence. Penelitian ini bertujuan untuk merancang dashboard monitoring kunjungan pada fasilitas kesehatan XYZ. Metode rekayasa perangkat lunak yang digunakan adalah metode prototyping. Dalam metode tersebut, identifikasi KPI (Key Performance Indicator) ditambahkan untuk menentukan tampilan visualisasi dashboard. Dalam hasil perancangan tersebut, visualisasi dashboard yang dirancang menggunakan alat Microsoft Power BI, akan menampilkan grafik diagram yang menunjukan data, serta dalam bentuk angka berupa KPI. Pengujian yang telah dilakukan akan memberikan pelayanan yang meningkat.Â